Embedded ZnO nanorods and gas-sensing properties - Shahid, Hussain; Tianmo, Liu; Bin, Miao; Muhammad, Kashif; Nimra, Aslam; Muhammad, Rashad; Wen, Zeng; Xianghe, Peng (Elsevier Ltd and Techna Group S.r.l., 2015)
Regular hexagonal embedded ZnO nanorods were successfully prepared by a simple hydrothermal method. The addition of urea as a homogeneous precursor was found to play a vital role in the embedding of secondary nanorods. The nanostructures were characterized by XRD, SEM, and EDS. The gas-sensing properties of secondary grown embedded nanorods were reported for formaldehyde, ethanol, methanol, acetone, and ammonia at different concentrations and temperatures. A higher response and greater selectivity toward formaldehyde than other gases was observed. A sharp response with the best recovery time was achieved at an optimum temperature of 200 °C.